Kajian Strategi Pengembangan Zona Air Minum Prima (Zamp) pada Kelompok Pelanggan Rumah Tangga di Kota Bogor (Studi Kasus: Eksisting Zamp di Kecamatan Bogor Selatan dan Bogor Timur) - Gumilar, Nurul Ainy (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2015)
PDAM Tirta Pakuan as the operator of water supply in Bogor city is very attentive to provide good drinking water services to the public, especially the distribution of potable water quality through a network of piping in some areas called Zona Air Minum Prima (ZAMP). The program has been ongoing since 2004, but until now the coverage is still low compared with the total customer taps in Bogor City. Under these conditions, a research that aims to formulate development strategies in Zona Air Minum Prima (ZAMP) for groups of households customer in Bogor City is conducted. Based on the results of the survey on medium (R3-R5) and the upper middle (R6-R8) households customer in the existing ZAMP and development plans ZAMP area in Taman Yasmin, there are similar characteristics to customers in both regions indicate development potential. Assessment of customer satisfaction on aspects of quality, quantity and continuity of water in the region showed a "good" score, but an assessment of the communication aspect of PDAM is not good, especially in terms of information provided by PDAM are judged less by the customer. Based on research conducted there can be formulated several strategies, such as communication strategy through early and advanced socialization, price or tariff adjustment strategy of potable water and an additional water filter installation strategy.